Gastrointestinal complications following on-pump cardiac surgery—A propensity matched analysis - Marsoner, Katharina (PLoS One, 2019)
BACKGROUND: Gastrointestinal complications following on-pump cardiac surgery are orphan but serious risk factors for postoperative morbidity and mortality. We aimed to assess incidence, perioperative risk factors, treatment modalities and outcomes. MATERIAL AND METHODS: A university medical center audit comprised 4883 consecutive patients (median age 69 [interquartile range IQR 60–76] years, 33% female, median logistic EuroScore 5 [IQR 3–11]) undergoing all types of cardiac surgery including surgery on the thoracic aorta; patients undergoing repair of congenital heart disease, implantation of assist devices or cardiac transplantation were excluded. Coronary artery disease was the leading indication for on-pump cardiac surgery (60%), patients undergoing cardiac surgery under urgency or emergency setting were included in analysis. We identified a total of 142 patients with gastrointestinal complications. To identify intra- and postoperative predictors for gastrointestinal complications, we applied a 1:1 propensity score matching procedure based on a logistic regression model. RESULTS: Overall, 30-day mortality for the entire cohort was 5.4%; the incidence of gastrointestinal complications was 2.9% and median time to complication 8 days (IQR 4–12). Acute pancreatitis (n = 41), paralytic ileus (n = 14) and acute cholecystitis (n = 18) were the leading pathologies. Mesenteric ischemia and gastrointestinal bleeding accounted for 16 vs. 18 cases, respectively. While 72 patients (51%) could be managed conservatively, 27 patients required endoscopic/radiological (19%) or surgical intervention (43/142 patients, 30%); overall 30-day mortality was 12.1% (p<0.001). Propensity score matching identified prolonged skin-to-skin times (p = 0.026; Odds Ratio OR 1.003, 95% Confidence Interval CI 1.000–1.007) and extended on-pump periods (p = 0.010; OR 1.006, 95%CI 1.001–1.011) as significant perioperative risk factors. COMMENT: Prolonged skin-to-skin times and extended on-pump periods are important perioperative risk factors regardless of preoperative risk factors.